Changes in male reproductive health and effects of endocrine disruptors in Scandinavian countries - Toppari Jorma; Haavisto Anne-Maarit; Alanen Markku (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
Male reproductive health has deteriorated in many ways during the last decades. The incidence of testicular cancer has rapidly increased in Europe and European-derived populations. Sperm concentrations have declined and sperm motility and morphology have worsened in many areas. Both adverse trends have been shown to be associated with year of birth. Older birth cohorts have better reproductive health than the younger generations. Incidences of cryptorchidism and hypospadias have also increased according to several studies. The reasons for secular trends are unknown, but the rapid pace of the change points to environmental causes. Endocrine disrupting chemicals have been hypothesized to influence male reproductive health.